Where the watermelons grow - Baldwin, Cindy (Harper, an imprint of HarperCollinsPublishers, 2018)
Twelve-year-old Della Kelly of Maryville, North Carolina, tries to come to terms with her mother's mental illness while her father struggles to save the farm from a record-breaking drought.